2005
DOI: 10.3310/hta9420
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of cognitive behaviour therapy clinical trials in central Scotland

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 104 publications
1
61
0
5
Order By: Relevance
“…In fact, research indicates that an early therapeutic alliance produces more positive treatment outcomes for clients in many areas of mental health, such as depression (Zuroff and Blatt, 2006) and anxiety (Durham et al, 2005). However, therapeutic relationships require effort and, even once formed, can be problematic.…”
Section: Illustration One: the Learning Alliancementioning
confidence: 99%
“…In fact, research indicates that an early therapeutic alliance produces more positive treatment outcomes for clients in many areas of mental health, such as depression (Zuroff and Blatt, 2006) and anxiety (Durham et al, 2005). However, therapeutic relationships require effort and, even once formed, can be problematic.…”
Section: Illustration One: the Learning Alliancementioning
confidence: 99%
“…Those that exist relate to CBT for relapse prevention 23 or CBT delivered in 'real time' over the internet using an instant messaging service. 24 Other reports on cost-effectiveness of CBT, for example, Durham et al, 25 are confined to different patient populations (anxiety/psychosis) and varied CBT interventions (including low-intensity interventions comprising, on average, four sessions with a contact time of just 2.6 hours) and cannot be generalised more widely.…”
Section: Defining Treatment Resistancementioning
confidence: 99%
“…A recent meta-analysis found that the controlled effect size (i.e., in comparison to a wait list) at follow up assessments is meaningfully lower than average controlled effect sizes at post-treatment (Sánchez-Meca, RosaAlcázar, Marín-Martínez, & Gómez-Conesa, 2010). Similarly, one of the longest follow-up studies followed 189 patients with panic disorder for up to 14 years following several different randomized trials and concluded that the short term effects are unrelated to long term outcomes (Durham et al, 2005). Similar conclusions were reached in a 15 year follow-up assessment following pharmacological treatment of panic disorder (Andersch & Hetta, 2003).…”
mentioning
confidence: 99%